Factors to Consider to Study Preductal Oxygen Saturation Targets in Neonatal Pulmonary Hypertension - Heather Siefkes; Sherzana Sunderji; Jessica Vaughn; Deepika Sankaran; Payam Vali; Pranjali Vadlaputi; Sage Timberline; Avni Bhatt; Daniel Tancredi; Satyan Lakshminrusimha (MDPI AG, 2022)
There are potential benefits and risks to the infant with higher and lower oxygen saturation (SpO2) targets, and the ideal range for infants with pulmonary hypertension (PH) remains unknown. Targeting high SpO2 can promote pulmonary vasodilation but cause oxygen toxicity. Targeting lower SpO2 may increase pulmonary vascular resistance, especially in the presence of acidosis and hypothermia. We will conduct a randomized pilot trial to compare two ranges of target preductal SpO2 in late-preterm and term infants with hypoxic respiratory failure (HRF) and acute pulmonary hypertension (aPH) of the newborn. We will assess the reliability of a newly created HRF/PH score that could be used in larger trials. We will assess trial feasibility and obtain preliminary estimates of outcomes. Our primary hypothesis is that in neonates with PH and HRF, targeting preductal SpO2 of 95-99% (intervention) will result in lower pulmonary vascular resistance and pulmonary arterial pressures, and lower the need for pulmonary vasodilators (inhaled nitric oxide-iNO, milrinone and sildenafil) compared to targeting SpO2 at 91-95% (standard). We also speculate that a higher SpO2 target can potentially induce oxidative stress and decrease response to iNO (oxygenation and pulmonary vasodilation) for those patients that still require iNO in this range. We present considerations in planning this trial as well as some of the details of the protocol design (Clinicaltrials.gov (NCT04938167)).